Investigating EFL Police Officers’ Learning Needs and Problems in English Listening and Speaking Skills: An English Specific Purposes (ESP) Context - I Made Ivan Prima Nugraha; Arif Rahman; Rimajon Sotlikova (Journal of Language and Literature Studies, 2024)
This research delves into the imperative nature of English speaking and listening competencies for tourist police officers and travel agents, crucial for efficacious communication with international tourists. Specifically, it focuses on the English linguistic needs and challenges faced by Mataram Police Officers (MPOs) stationed at the Mataram Town Police Station’s counter. Adopting a qualitative methodology, the study employs questionnaires and interviews to gather data, involving a cohort of 15 police officers from Mataram as participants. The findings illuminate that MPOs necessitate enhancement in their English listening and speaking abilities across several critical functions. These include extending greetings and assistance, soliciting personal information, understanding tourists’ issues and desires, and providing details on accommodations, travel, transportation, emergency services, directions, and advice on safety, travel, and shopping. The study reveals that for effective participation in English training programs, MPOs emphasize the need for proficiency in basic conversational English, advocating for the study of English textbooks and practical dialogue exercises. It is suggested that English training sessions be conducted over weekends, with each session lasting 1.5 hours, spanning a three-month period. The preference for instructors includes Thai teachers alongside native English speakers. The research further identifies the primary challenges in listening and speaking faced by the MPOs. Listening difficulties are predominantly attributed to the varied English accents, the challenge in capturing main ideas, and understanding fundamental expressions. Conversely, the speaking impediments involve articulating basic expressions, constructing complete sentences, and the pronunciation of English vowels. This study not only highlights the linguistic gaps in the professional capabilities of MPOs but also proposes targeted educational interventions to bridge these gaps, underscoring the significance of tailored English language training in enhancing the tourism policing experience.